Automotive teaching aid with instrumentation for Morris Marina (3L engine part 3) / Azman Mohd Said, Mohamed Noor Baba and Mohd Nasir Ab. Manaf - Mohd Said, Azman; Baba, Mohamed Noor; Ab. Manaf, Mohd Nasir (1987)
The aim of this project is to get a better engine with good petrol consumption and with the add of a electrical wiring with instrumental for a 1970 Morris Marina 1.3 cc four stroke engine. To achieved better consumption the cylinder chamber, inlet part and intake manifold have been carefully and thoroughly grounded and polished and engine should) properly tunned according to specification. When this project was completely done it can be used for teaching practically for a subject of Automobile Technology.